Increased Interest in Science Learning Through Integrated Learning of Local Snacks with The Discovery Learning Model - Nisa, Wilda Muhimmatun; Wilujeng, Insih; Pradana, Diego (Universitas Negeri Malang, 2020)
This study aimed to determine the interest in learning science after using integrated learning of local snacks in Cangkringan with Discovery Learning model at Cangkringan Junior High School 1. This study is a pre-experimental design that used a onee-group pretest-posttest design. The sample in this study were 31 students of class VIIIA lesson 2019/2020. Data collection techniques by using a observation and questionnaire of interest in learning before and after treatment in order to measure student interest in learning. Observations carried out by holding observations of activities that are taking place in class. The indicator of learning interest instruments, in the questionnaire is interest, pleasure, attention, and desire or awareness. Learning interest data generated in the form of scores (quantitative data) with 4 scale were strongly agree (SS), agree (S), less agree (KS), and disagree (TS). The questionnaire was developed by researchers by showing indicators of interest in learning with 23 questions. Data analysis techniques by using N-Gain analysis techniques and descriptive analysis by converting the results of percentage analysis. the result showeed that the students' interest in learning science after implementation of integrated learning of local potential with discovery learning models increases with an N-gain score of 0.59 in the medium category. The average percentage value of descriptive analysis of student learning interest has increased from 72.01 percent with moderate criteria to 88.56 percent with high criteria.